Efektivitas Media Gambar dan Kata-kata dalam Pembelajaran Bahasa Inggris pada Siswa Kelas 6 SD - Lusia Gayatri (LPPM Universitas Proklamasi 45, 2010)
Many researches revealed that picture method was useful to increase children’s ability to recognize concrete objects. In order to bridge children's difficulty in learning English as a foreign language, this research was aimed to increase children’s recognize on some new English words. Learning English based on conventional method (using many words only) was compared experimentally with picture method. Seventy students grade sixth from 4 elementary schools participated in this study. Design of this experimental study was the pretest - post test. The intervention was conducted once during 75 minutes i.e. 50 minutes for exercising English words using pictures (for the picture group) and words (for the word group); 10 minutes for conducting a quiz; and 15 minutes for verifying the exam questions. It was hypothesized that the picture method was much better to increase children’s ability to recognize some new English words than the conventional method. This research revealed that children’s ability on the picture method class increased 2.5 times from the pre test compared to children in word method class (increased only 1.7 times from the pre test) and children in the control group (increased only 1.06 times from the pre test and non significant). It was recommended that teacher should use pictures to help children to understand English new vocabularies. This recommendation could also be enlarged with comic and animated film usages.